Need for national guidance regarding proactive care of infants born at 22–23 weeks' gestation - Ga Won Jeon (Clinical and Experimental Pediatrics)
With recent rapid improvements in neonatal intensive care, the limit of viability has shifted downward to 22–23 weeks' gestation. The younger the gestational age of preterm infants, the higher the risk of survival despite severe neurodevelopmental impairments. For infants born at 22–23 weeks' gestation, the limit of viability, neurodevelopmental outcomes, and survival rates may be determined by the quality of proactive care. Owing to the high risk of severe neurodevelopmental impairment in 22–23 weeks' gestation, proactive care is sometimes withheld according to ethical or legal considerations, and there are significant differences in the provision of proactive care and survival rates across countries or institutions. Additionally, there are differing or even lacking guidelines regarding the care of these infants across countries and institutions. Japan and Sweden are countries with well-established national guidance and proactive care for infants born at 22–23 weeks’ gestation, resulting in higher survival rates among them. In Korea, where there is an extreme shortage of neonatologists, maternal transfer before delivery at 22–23 weeks' gestation to high-activity regions with appropriate neonatal intensive care unit resources, such as adequate personnel and facilities similar to the centralized care model seen in Sweden, is crucial for improving the survival rates of infants born at 22–23 weeks' gestation. The survival of these infants largely depends on the quality of proactive care provided. This rate is not static and can be improved through proactive care based on national guidance and the implementation of enhanced neonatal intensive care practices, including centralization of care.